Pediatric central giant cell granuloma: exeresis, second-management and homeopathy - Agnaldo Rocha Prata Júnior; Alline Batistussi França; André Gustavo Santos Silva; Cléverson Luciano Trento; Wilton Mitsunari Takeshita; Liane Maciel de Almeida Souza (Editorial Ciencias Médicas, 2019)
Introduction: Giant cell central lesion is characteristic of the gnathic bones, being a non-odontogenic benign tumor. Classified as a predominantly slow grotwh, well-circumscribed and asymptomatic lesion usually diagnosed through routine examination or in some and more advanced cases once it begins to create some aesthetic-anatomical alteration or when the patient starts complaining of some located discomfort in the region. Objective: To present a clinical case of central giant cell lesion and its resolution involving surgical approach and second management, which includes homeopathy as a therapeutic proposal.Case presentation: central giant cell lesion located in the premaxilla region in a 4 years old female patient. After radiographic, tomographic and blood exams evaluation, followed by incisional biopsy and diagnostic, leading to surgical approach to remove the entire lesion by curettage with Carnoy's solution application under general anesthesia. After appearance of radiopaque imaging in the proservation examinations, the non-invasive treatment by corticoid injection and homeopathy got started aiming the reduction of cicatricial tissue's suggestive area and neoformation of the bone.Conclusions: approaches that are more conservative can be, in many cases, a plausible option that ends up ridding the patient of mutilating surgeries.